Longitudinal analysis of immune responses to SARS-CoV-2 recombinant vaccine S-268019-b in phase 1/2 prime-boost study - Fujitani, Masaya; Lu, Xiuyuan; Shinnakasu, Ryo; Inoue, Takeshi; Kidani, Yujiro; Seki, Naomi M.; Ishida, Satoru; Mitsuki, Shungo; Ishihara, Takeshi; Aoki, Miwa; Suzuki, Akio; Takahashi, Koji; et al. (Frontiers in Immunology, 2025)
BackgroundThe durability of vaccine-induced immune memory to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is crucial for preventing infection, especially severe disease.MethodsThis follow-up report from a phase 1/2 study of S-268019-b (a recombinant spike protein vaccine) after homologous booster vaccination confirms its long-term safety, tolerability, and immunogenicity.ResultsBooster vaccination with S-268019-b resulted in an enhancement of serum neutralizing antibody (NAb) titers and a broad range of viral neutralization. Single-cell immune profiling revealed persistent and mature antigen-specific memory B cells and T follicular helper cells, with increased B-cell receptor diversity. The expansion of B- and T-cell repertoires and presence of cross-reactive NAbs targeting conserved epitopes within the receptor-binding domain following a booster accounted for the broad-spectrum neutralizing activity.ConclusionThese findings highlight the potential of S-268019-b to provide broad and robust protection against a range of SARS-CoV-2 variants, addressing a critical challenge in the ongoing fight against coronavirus disease 2019 (COVID-19).